Relationship between training status and maximal fat oxidation rate - Lima-Silva, A. E.; Bertuzzi, R. C. M.; Pires, F. O.; Gagliardi, J. F. L.; Barros, R. V.; Hammond, J.; Kiss, M. A. P. D. M. (Journal of Sports Science & Medicine, 2010)
This study aimed to compare maximal fat oxidation rate parameters between moderate- and low-performance runners. Eighteen runners performed an incremental treadmill test to estimate individual maximal fat oxidation rate (Fatmax) based on gases measures and a 10,000-m run on a track. The subjects were then divided into a low and moderate performance group using two different criteria: 10,000-m time and VO2max values. When groups were divided using 10,000-m time, there was no significant difference in Fatmax (0.41 ± 0.16 and 0.27 ± 0.12 g.min-1, p = 0.07) or in the exercise intensity that elicited Fatmax (59.9 ± 16.5 and 68.7 ± 10.3 % O2max, p = 0.23) between the moderate and low performance groups, respectively (p > 0.05). When groups were divided using VO2max values, Fatmax was significantly lower in the low VO2max group than in the high VO2max group (0. 29 ± 0.10 and 0.47 ± 0.17 g.min-1, respectively, p < 0.05) but the intensity that elicited Fatmax did not differ between groups (64.4 ± 14.9 and 61.6 ± 15.4 %VO2max). Fatmax or %VO2max that elicited Fatmax was not associated with 10,000 m time. The only variable associated with 10,000-m running performance was %VO2max used during the run (p < 0.01). In conclusion, the criteria used for the division of groups according to training status might influence the identification of differences in Fatmax or in the intensity that elicits Fatmax.